Захист конфіденційності розмов по мобільному телефону - Катрич, О. О. (ХНУРЕ, 2023)
Current level of technology and cryptography development implies a wide range of special approaches of getting an unauthorized access to different devices and data they contain, including mobile phones. Confidentiality of phone conversations is highly threatened by spy software, attacks on cellular networks, unreliable messengers, means of acoustic data retrieval etc. However, there is a list of measures that prevent mobiles from illegal access and loosing privacy. Digital and hardware scrambling, high-secured messengers, detection means of acoustic intelligence devices and cryptophones are certain ways to tackle the problem.
Keywords: конфіденційність розмов